TATTO0 MEANING RECONSTRUCTION IN TATTOO COMMUNITY MEMBERS - Amir Dedoe (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
This study aims to examine the meaning of the reality of individual social interest in body art tattooing or tattooing as an identity so that they bind themselves into a social community. Tattoos in Indonesia with the inherent negative stigmatization, have the complexity of debate in the dynamics of their presence in the public sphere. This paper presents one perspective, especially from the point of view of tattoo owners regarding their perceptions of the motives for tattooing that they do. By conducting observations and in-depth interviews in an effort to make a qualitative scientific explanation of the ownership motives of tattoos by community members. By triangulation techniques, the author builds a constructivist framework of perception of tattoos in the community. This study found that a person's main motivation for having a tattoo is preceded by a desire to express artistic or artistic desires. When this accumulation of shared desires takes place, business motives and identity construction become a trigger for the formation of the tattoo community